Refractive surgery nightmare - Mohd. Kamal, Khairidzan (2015)
Anything can go wrong during surgery and we all like to live vicariously by watching other surgeons’ complications. Come to participate, commiserate, and criticize our faculty of surgeons who will present videos and case reports of their surgical nightmares. Listen, watch, and learn from the problems encountered by this faculty of refractive surgeons so that you don’t have to relive the nightmares yourself.